2007
DOI: 10.1111/j.1365-294x.2006.03139.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale spatial genetic structure and dispersal among spotted salamander (Ambystoma maculatum) breeding populations

Abstract: We examined fine-scale genetic variation among breeding aggregations of the spotted salamander (Ambystoma maculatum) to quantify dispersal, interpopulation connectivity and population genetic structure. Spotted salamanders rely on temporary ponds or wetlands for aggregate breeding. Adequate breeding sites are relatively isolated from one another and field studies suggest considerable adult site fidelity; therefore, we expected to find population structure and differentiation at small spatial scales. We used mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
97
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(107 citation statements)
references
References 92 publications
(100 reference statements)
9
97
0
1
Order By: Relevance
“…The F ST values obtained were higher than those documented in other fine-scale salamander studies (Cabe et al, 2007;Zamudio and Wieczorek, 2007;Purrenhage et al, 2009) and frog island populations (Lind et al, 2010), but showed similar levels of divergence to other amphibian population genetic studies covering larger regions (Spear et al, 2005;Savage et al, 2010). The similarities in genetic diversity and demographics among island and coastal populations (Table 1; Figure 3) underscore their similar histories, despite the current differences in connectivity to the mainland.…”
Section: Island Isolation Vs Seawater Colonizationmentioning
confidence: 40%
“…The F ST values obtained were higher than those documented in other fine-scale salamander studies (Cabe et al, 2007;Zamudio and Wieczorek, 2007;Purrenhage et al, 2009) and frog island populations (Lind et al, 2010), but showed similar levels of divergence to other amphibian population genetic studies covering larger regions (Spear et al, 2005;Savage et al, 2010). The similarities in genetic diversity and demographics among island and coastal populations (Table 1; Figure 3) underscore their similar histories, despite the current differences in connectivity to the mainland.…”
Section: Island Isolation Vs Seawater Colonizationmentioning
confidence: 40%
“…With microsatellites, r-values of 0.015-0.06 in Rana temporaria (Johansson et al, 2005) and ca. 0.06 in spotted salamanders, Ambystoma maculatum (Zamudio and Wieczorek, 2007), were reported. Moran's-I of single minisatellite alleles in Bufo bufo in Great Britain ranged widely, from À0.03 to 0.07 (Scribner et al, 2001).…”
Section: Kr Elmer Et Almentioning
confidence: 99%
“…Pondbreeding amphibians provide especially good study systems for examining the effects of aquatic breeding habitats on population parameters, because breeding ponds have quantifiable features and often demarcate discrete yearly cohorts of breeding populations. Additionally, amphibians are facing local and global declines (Fisher and Shaffer 1996;Houlahan et al 2000;Collins and Storfer 2003;Stuart et al 2004) and are often sensitive to anthropogenic habitat alteration (Guerry and Hunter 2002;Zamudio and Wieczorek 2007). Thus, studies linking breeding habitat and population persistence may play a critical role in conservation and management strategies (Gibbs 1998;Guerry and Hunter 2002;Funk et al 2005;Rittenhouse and Semlitsch 2006).…”
Section: Introductionmentioning
confidence: 99%